Evaluation of the sensory perception of sweet taste in people with Diabetes Mellitus type 2 - Vanéria Ribeiro Dias; Jamille Marinho Brazil; Juliane Angelica Reges Almeida; Camile de Souza Silva; Maria Patrícia Milagres (Rev Rene)
Objective: to evaluate the perception of patients with type 2 diabetes through the threshold index test for the sweet taste. Methods: a cross-sectional study with 80 adults of both genders, divided into two groups: control, composed of non-diabetics, and test, with diabetic patients. The evaluation of sensory perception held by the sensitivity test to determine the threshold index. The tests were conducted on five sections containing different concentrations of sucrose. Statistical analysis was held using the t test, adopted P<0.05. Results: when comparing the average of the thresholds to detect sweet taste between diabetics and non-diabetics, it was known that diabetics are less sensitive to sweet stimuli. Conclusion:individuals with Diabetes Mellitus 2 have higher threshold index value for the sweet taste, which may contribute to the increase in sugar consumption.